2015
DOI: 10.1007/978-3-319-13865-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Detecting CDOM Fluorescence Using High Spectrally Resolved Satellite Data: A Model Study

Abstract: Absorption and fluorescence of CDOM are widely used to characterize its concentration and composition, both in situ and with remote sensing techniques. As fluorescence is an inelastic scattering process, it can potentially be observed in filling-in of Fraunhofer lines with the DOAS method in high spectrally resolved satellite data. Here, we perform a theoretical model study and preliminary DOAS retrieval on SCIAMACHY data in order to test the feasibility of such an approach. Our results show that retrieving CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The study by Wolanin et al [90] used the presented SCIATRAN package to simulate CDOM fluorescence in ocean waters and confirms the applicability of the model also to case 2 waters. As in the radiative transfer simulations based on matrix-operator by Schröder et al [64], it was shown that only in case 2 waters with very high CDOM concentrations, CDOM fluorescence can reach or exceed the relevance of VRS at short wavelengths.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The study by Wolanin et al [90] used the presented SCIATRAN package to simulate CDOM fluorescence in ocean waters and confirms the applicability of the model also to case 2 waters. As in the radiative transfer simulations based on matrix-operator by Schröder et al [64], it was shown that only in case 2 waters with very high CDOM concentrations, CDOM fluorescence can reach or exceed the relevance of VRS at short wavelengths.…”
Section: Discussionmentioning
confidence: 68%
“…However, for the development of such retrievals precise measurements of these spectra accompanied by correctly determined molar absorbance, quantum efficiency and concentrations of these components and the separation of their filling-in of Fraunhofer lines from VRS and RRS are needed. This SCIATRAN package would be suitable to develop these retrievals as it has been done for the marine chl-a fluorescence in [90].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All terms are a function of depth z and wavelength λ. The Zaneveld expression does not account for any inelastic processes, such as molecular Raman scattering or fluorescence [30][31][32][33]. Using physically reasoned approximations for f b including the assumption of single scattering, the following was obtained by Zaneveld ([28]; his Equation 14):…”
Section: Forward Model Developmentmentioning
confidence: 99%